2019
DOI: 10.7575/aiac.ijels.v.7n.1p.59
|View full text |Cite
|
Sign up to set email alerts
|

Role of Prosodic Reading in Listening Comprehension

Abstract: This study aims to determine how listening comprehension levels of students are affected by listening to prosodic and non-prosodic readings vocalized by a computer and human. Third-grade students of four different classes at a primary school were randomly selected in a city center in the Western Black Sea Region of Turkey to participate in the study (n=91). Four equivalent classes formed the listening groups of the research in listening comprehension. The groups were (1) the group listening to the model prosod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Van Wijngaarden (2001) showed that speech recognition in Dutch was negatively affected (a 3-dB raising of the speech reception threshold) for Dutch native listeners when the stimulus materials, whether spoken by native Dutch or nonnative English-accented speakers, were artificially monotonized. Recently, Keskin et al (2019) reported that listening comprehension by Turkish primary schoolers suffered when all prosodic information was removed from a Turkish spoken text, at least when the questions required inferential listening (but not when literal content questions were asked). Luu et al (2021) concluded that prioritizing prosody by using the techniques such as listening to low-pass filtered audio, repetition in synchrony with body movements, and shadowing, enhances listening comprehension skills.…”
Section: The Importance Of Listening Comprehension For Interpretingmentioning
confidence: 99%
“…Van Wijngaarden (2001) showed that speech recognition in Dutch was negatively affected (a 3-dB raising of the speech reception threshold) for Dutch native listeners when the stimulus materials, whether spoken by native Dutch or nonnative English-accented speakers, were artificially monotonized. Recently, Keskin et al (2019) reported that listening comprehension by Turkish primary schoolers suffered when all prosodic information was removed from a Turkish spoken text, at least when the questions required inferential listening (but not when literal content questions were asked). Luu et al (2021) concluded that prioritizing prosody by using the techniques such as listening to low-pass filtered audio, repetition in synchrony with body movements, and shadowing, enhances listening comprehension skills.…”
Section: The Importance Of Listening Comprehension For Interpretingmentioning
confidence: 99%
“…Quantitative data of the study were obtained by using the "Prosodic Reading Scale" (PRS) validated by Keskin, Baştuğ, and Akyol (2013) and PRAAT audio analysis software.…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…Van Wijngaarden (2001) has shown that speech recognition in Dutch was negatively affected (a 3-dB raising of the speech reception threshold) for Dutch native listeners when the stimulus materials, whether spoken by native Dutch or non-native English-accented speakers, were artificially monotonised, thus highlighting the importance of prosody to comprehension. Keskin et al (2019) have also reported that L1 listening comprehension by Turkish primary schoolers suffered when all prosodic information was removed from a Turkish spoken text, at least when the questions required inferential listening (though not when literal content questions were asked). Luu et al (2021), concluded that prioritising prosody by using techniques such as listening to low-pass filtered audio, repetition in synchrony with body movements, and speech shadowing, enhance the English listening comprehension skills of Vietnamese college freshmen.…”
Section: Introductionmentioning
confidence: 99%